Prison administration privatisation: Practices, issues and prospects - Dhameja, Nand; Singh, Rajesh (1999)
Looking at some burgeoning problems in prison administration, the authors probe finding solutions thereof through privatisation of prison administration functions. Attempting to be sure-footed, they first provide relevant international experience on the subject from the developed world, then examine major issues involved in privatisation exercise in this rather sensitive area, and top it with a suggestive framework which, according to them, would help realise privatisation of prison administration in India. - Reproduced
Keywords: Privatization; Prisoners